Synthesizing Recent Trends in Interventions and Key Ecosystem Services in Indonesian Peatland - Hyun-Ah Choi; Cholho Song; Chul-Hee Lim; Woo-Kyun Lee; Hyunyoung Yang; Raehyun Kim (Land, 2024)
This study conducted a systematic literature review focusing on peatlands studies in Southeast Asia, specifically in Jambi, South Sumatra, and the Riau province of Indonesia, covering the period from 2001 to 2023. To ensure the quality and rigor of the analyzed articles, a critical process and systematic review were employed. Journal articles were extracted using reputable resources, including Google Scholar and Scopus, to enhance the validity and reliability of the research results. We identified significant research topics based on region, province, and sector. Additionally, we synthesized the existing classification of ecosystem services, drawing on previous studies conducted in Indonesia. These services were categorized as provisioning, regulating, cultural, and supporting services. We also reviewed the classification of ecosystem service types based on peatland degradation and restoration. This study identified evidence of peatland intervention to evaluate ecosystem services in Indonesia. We found that large-scale cultivation and production of palm oil, local policies, and forest fires were the main intervening factors in Indonesian peatlands. Furthermore, Indonesian peatlands have undergone conversion to oil palm, timber, and crop plantations. It is imperative to substantiate the effectiveness of future peatland restoration plans and further refine the quantification of services provided by peatland ecosystems through cooperative projects.